2020
DOI: 10.1088/1361-6641/aba168
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of native point defects and photocatalytic activity of annealed ZnO nanoparticle studied by electron spin resonance and photoluminescence emission

Abstract: In this paper, we investigate the origin of point defects revealed by electron spin resonance (ESR) and photoluminescence (PL) emission in correlation with the photocatalytic activity of ZnO nanocrystals subjected to thermal annealing at various temperatures. Two ESR signals at g ∼ 1.96 and ∼2.003 were consistently observed in all annealed ZnO samples. However, their relative intensities have changed, indicating that the point defect densities were influenced by the annealing temperature. Interestingly, when d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Upon H 2 reduction, a signal at g = 2.004 appears and no other signals are observed over nanoflakes. g = 2.004 signal was frequently reported to be related to the presence of a free electron in the conduction band 37 , 38 , or defect sites over singly ionized zinc vacancy of zinc-based oxides 32 , 39 42 . However, it was also assigned to unpaired electron trapped at an oxygen vacancy site of oxides such as ZnO 35 , 41 , 43 , Zn x Ga y O z 37 , 44 , 45 , or TiO 2 38 , 46 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon H 2 reduction, a signal at g = 2.004 appears and no other signals are observed over nanoflakes. g = 2.004 signal was frequently reported to be related to the presence of a free electron in the conduction band 37 , 38 , or defect sites over singly ionized zinc vacancy of zinc-based oxides 32 , 39 42 . However, it was also assigned to unpaired electron trapped at an oxygen vacancy site of oxides such as ZnO 35 , 41 , 43 , Zn x Ga y O z 37 , 44 , 45 , or TiO 2 38 , 46 .…”
Section: Resultsmentioning
confidence: 99%
“…However, it was also assigned to unpaired electron trapped at an oxygen vacancy site of oxides such as ZnO 35 , 41 , 43 , Zn x Ga y O z 37 , 44 , 45 , or TiO 2 38 , 46 . The assignment of g = 1.97 also remains controversial in different studies, e.g., singly ionized oxygen vacancies with one trapped electron 33 , 47 , zinc vacancies 42 , 48 , 49 , or donor centers such as ionized impurity atoms in the crystal lattice of ZnO oxide 50 , 51 . Volatility of zinc species has been frequently reported for ZnO and Zn-based oxides, which is facilitated in vacuum and hydrogen atmosphere 52 – 55 .…”
Section: Resultsmentioning
confidence: 99%
“…The Zn1-xCuxO samples with x = 0.0 and 0.01 were prepared by sol-gel method similar to previous reports [10,11]. Typically, the zincnitratehexahydrate -Zn(NO3)2.6H2O (Sigma-Aldrich) and copper(II) nitrate trihydrate -Cu(NO 3 )2.3H2O (Sigma-Aldrich) were mixed with citric acid -C6H8O7.H2O 1M (Sigma-Aldrich) with a molar ratio of metal ions : acid = 1:3.…”
Section: Methodsmentioning
confidence: 99%
“…The fitting decay curves of timeresolved PL spectra shown in the subfigure of Figure 6(b) indicated that the photoelectron lifetime of TNT/Ag of ~4.26 ns was significantly longer than that of TNT, which was ~1.68 ns. Hence, the recombination rate of the composite sample was about 2.75-fold longer than that of TNT; thus, photoexcited carriers would have more time in the solution vicinity to promote highly oxidative and reductive radicals to decompose the organic dye [49,50].…”
Section: Surface Morphological and Structural Propertiesmentioning
confidence: 99%